Extended analysis of the high resolution FTIR spectra of H2MS (M=32, 33, 34, 36) in the region of the bending fundamental band: The ν2 and 2ν2−ν2 bands: Line positions, strengths, and pressure broadening widths. (September 2018) - Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Glushkov, P.A.; Scherbakov, A.P.; Horneman, V.-M.; Sydow, C.; Maul, C.; Bauerecker, S.
Highlights: High resolution analysis of H 2 ( M ) S ( M = 32, 33, 34, 36 ) FTIR spectra. The v2 band: line positions, strengths, half-widths. Determination of spectroscopic parameters. Abstract: The high resolution infrared spectra of hydrogen sulfide, H2 M S ( M = 32, 33, 34, 36 ) in the natural abundance (95.041% of H2 32 S, 0.748% of H2 33 S, 4.196% of H2 34 S and 0.015% of H2 36 S), were recorded with a Bruker IFS 125HR Fourier transform infrared spectrometer (Zürich prototype ZP2001) and analyzed in the ν 2 fundamental band region (700 – 1800 cm − 1 ). In the experimental spectra 1564, 1019, and 685 transitions were assigned to the ν 2 bands of H2 32 S, H2 34 S and H2 33 S (the maximum values of the quantum numbers are J m a x . / K a m a x . = 24/17, 20/14, 17/14). The subsequent weighted fits of experimentally assigned transitions were made with the Watson Hamiltonian and a set of parameters which reproduces the initial 333/249/216 infrared ro-vibrational energy values has been obtained from the assigned experimental line positions with the root mean square deviations of d r m s = 2.2 × 10 − 4 cm − 1, 1.7 × 10 − 4 cm − 1 and 1.5 × 10 − 4 cm − 1 for the H2 32 S, H2 34 S and H2 33 S isotopologues. Additionally, 703, 182 and 23 transitions with the values of quantum numbers J m a x . / K a m a x . = 18/14, 14/8 and 9/6 belonging to the 2 ν 2 − ν 2 hot bands of H2 32 S, H2 34 S and H2 33 S (for the first time for the hot bands of the H2 34 S and H2 33 S species) were assigned in the experimental spectra. Rotational parameters of the ground vibrational state of H2 36 S were re-determined, and, for the first time, 103 transitions ( J m a x . = 11, K a m a x . = 8 ) of the ν 2 band of H2 36 S were assigned in the experimental spectra. An analysis of ro-vibrational line strengths of 61 experimental isolated unsaturated and not too weak lines of the ν 2 band of H2 32 S was made ( J m a x . = 9, K a m a x . = 8 ), and five effective dipole moment parameters were obtained from the fit which reproduce the initial experimental line intensities with the d rms = 1.4 %. An analogous analysis was performed for the H2 34 S and H2 33 S isotopologues. The half-widths analysis was made on the basis of the multi-spectrum fit with the Hartmann-Tran line profile, and self-pressure broadening coefficients were estimated for a few tens of lines for the three most abundant isotopologues.